Zoning Standards and Compliance in the Context of Customary Tenure System : A Case Study of West Ashiyie, Adentan Municipality in Ghana - Matey, E. (2020)
Land use planning, through zoning regulations, is the regulatory component of land administration. For residential areas for example, zoning regulations detail the types of buildings and standards for setbacks, minimum parcel size, maximum plot coverage etc. This study assessed the implementation of zoning standards in areas under customary land tenure in Ghana. Customary authorities allocate land rights to individuals, while the Municipality’s planning authority oversees the implementation of zoning standards. A case study approach is used to establish the factors that influence land right holders (under customary tenure system) to comply with residential standards; how enforcement (by the Municipality) ensures the implementation of zoning standards. Spatial conformity between the vector data extracted from local plans overlayed over the orthophoto from 2014 was analyzed. Results show a high compliance with the permitted land use i.e. residential area, although residents breached on the maximum plot coverage as compared to other standards. Residents are ignorant of the details of the zoning standards and have never seen a zoning regulations document. There is also a low level of monitoring and enforcement. Most respondents have never encountered the monitoring and enforcement team. Spatial analysis reveals four main types of non-conformity between orthophoto and local plans i) discrepancies in the orientation of the parcel boundaries, ii) discrepancies in the shapes of plot boundaries, iii) houses constructed on the plot boundary or straddle parcel boundaries, and iii) differences in plot sizes. Results suggest the need for planning authority to use efficient approaches to communicate, monitor and enforce the zoning standards. It is concluded that collaboration between customary land authorities and the Municipality during the allocation of plots may improve spatial conformity between orthophoto and the local plans.